PENGARUH KOMPETENSI DAN TEKANAN WAKTU TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (FRAUD) LAPORAN KEUANGAN PADA KANTOR AKUNTAN PUBLIK (KAP) DI KOTA BANDUNG - Ade Pipit Fatmawati; Nazura Atikafani (Universitas Logistik dan Bisnis Internasional, 2026)
The inability of Public Accounting Firms to expose fraud, particularly financial reporting, raises public doubts about the ability, quality, and integrity of external auditors. The study pursues the objective of investigate the impact of proficiency as well as time constraints on auditors' expertise in detecting misstatements within financial statements. The present study employs a quantitative methodology involving a population of 87 auditors from Audit Firms (KAP) across Bandung Municipality, using a total sampling technique. Primary were acquired by means of a questionnaires and subsequently analyzed with SPSS version 27, including descriptive statistics, validity and reliability tests, normality tests, correlation analysis, multivariate regression, partial tests, anova f-tests, and coefficient of determination. The findings reveal that proficiency has a partial influence on auditors’ aptitude for spotting fraud in financial statements, whereas time pressure provides no evidence of a partial influence on auditors' capacity to expose fraud in financial statements. Simultaneously, competence and time pressure influences auditors’ capability to uncovering fraud in financial statements